A novel engineering process for spatial opto-mechatronic applications. Issue 1 (2016) - Franke, Jörg; Zeitler, Jochen; Reitberger, Thomas
Abstract: Well-known advantages of optical data communication, like high-speed data transmissions and higher integration densities, are the main drivers for novel applications in the field of opto-electronics. A new innovative approach is to print polymer optical waveguides on spatial circuit carriers. This allows creating highly integrated devices that unify the characteristics of electro-optical circuits with the advantages of 3D-mechatronic integrated devices (MID). This paper describes the introduction of a novel engineering method that includes technology-specific processes for creating new spatial opto-mechatronic applications with the focus on printing technologies and computer-aided design.